2021
DOI: 10.3390/children8020148
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Non-Referential Gestures: A Systematic Review of Their Cognitive and Linguistic Effects in Children’s Language Development

Abstract: Speakers produce both referential gestures, which depict properties of a referent, and non-referential gestures, which lack semantic content. While a large number of studies have demonstrated the cognitive and linguistic benefits of referential gestures as well as their precursor and predictive role in both typically developing (TD) and non-TD children, less is known about non-referential gestures in cognitive and complex linguistic domains, such as narrative development. This paper is a systematic review and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 104 publications
2
19
1
1
Order By: Relevance
“…On the other hand, our results also reinforce the predictive value of non-referential gestures found in Vilà-Giménez et al’s (2021a) study, supporting the idea that these gestures may play an important discourse-pragmatic role starting early in children’s language development. Overall, our results strongly support the view that the bootstrapping and predictive role of non-referential gestures in children’s narrative development has its roots in their pragmatic and discursive properties, and they may be key when explaining why non-referential gestures have been reported to be so relevant in children’s narrative discourse abilities (see Vilà-Giménez and Prieto, 2021 , for a review).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…On the other hand, our results also reinforce the predictive value of non-referential gestures found in Vilà-Giménez et al’s (2021a) study, supporting the idea that these gestures may play an important discourse-pragmatic role starting early in children’s language development. Overall, our results strongly support the view that the bootstrapping and predictive role of non-referential gestures in children’s narrative development has its roots in their pragmatic and discursive properties, and they may be key when explaining why non-referential gestures have been reported to be so relevant in children’s narrative discourse abilities (see Vilà-Giménez and Prieto, 2021 , for a review).…”
Section: Discussionsupporting
confidence: 81%
“…Importantly, we suspect that the ability to use manual non-referential gestures to mark IS might be related to children’s more complex cognitive and linguistic processes, such as narrative or pragmatic abilities (see Vilà-Giménez and Prieto, 2021 , for a review), or more complex cognitive skills, such as Theory of Mind (ToM; e.g., Carmiol and Sparks, 2014 ; Graf and Davies, 2014 ), which emerge and evolve at this stage in development. While research has demonstrated the link between non-referential gestures and narrative development, as far as we know, there is no previous study that assesses how these gestures relate to ToM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies in this Special Issue describe important factors that affect language development at different ages, thus depicting several key aspects to be considered in the prevention of communication and language difficulties throughout childhood. These studies range from the beginnings of word production [4] or gestures [5] to the impact of the use of technological devices in preadolescent children [6]. In addition, they cover different aspects or linguistic components, from phonetics [7], vocabulary [4], or syntax [8], to non-referential gestures related to narrative development [5].…”
Section: Markers Of Language Developmentmentioning
confidence: 99%
“…After analysis [21,22], gesture behaviours were mostly expressed by index finger depiction, such as writing and drawing. Capturing index finger behaviour required collecting the following feature values: three components of position, three components of rotation angle, and three components of an index finger, as shown in Figure 3.…”
Section: Gesture Command Definitionmentioning
confidence: 99%